Analisis Pengelolaan Sampah Rumah Tangga Berbasis Edukasi Di Kecamatan Selebar - Anggun Dwi Utami; Abditama Srifitriani; Yanmesli Yanmesli (Jurnal Georafflesia: Artikel Ilmiah Pendidikan Geografi, 2022)
The purpose of this study was to analyze the waste management of housewives in Selebar District, and to analyze the obstacles faced in managing the waste of housewives in the District. The type of research used was qualitative research. The results showed that (1) Waste management in Selebar District is still low. In general, housewives in Selebar District have less knowledge in terms of waste management (2) The obstacles faced by housewives in Selebar District include low technological developments, lack of waste management to improve people's living standards, supervision and implementation related to waste management, lack of community participation related to waste management. So with this problem, education or socialization of housewives is needed. Based on the results of research conducted on proper waste management education, namely an independent waste management system by applying the 5R+1FS principle (Reduce, Reuse, Recycle, Replace, Replant, Final Separation). Furthermore, socialization or education is given to housewives in the form of brochures to facilitate housewives in receiving information related to good and correct waste management and can change the mindset (thoughts) of housewives about waste. Keyword: Education, Household Waste Management